A secure online examination system - Saiful Mu'min Mohd Ariff (Nanyang Technological University, 2022)
Online examination systems have gained popularity in the education industry due to rapid growth in information and communication technologies (ICT). They stand out due to their high efficiency in managing resources such as time and manpower as compared to conventional examinations. With the recent COVID-19 pandemic, most educational institutions had no choice but to conduct examinations remotely to safeguard the health of their students while still being able to fulfil the requirements of their education assessments. Therefore, this increases the demand for more online examination systems to be developed. However, there are some challenges to preventing academic dishonesty from students due to the nature of online examinations. The project’s objective is to develop a secure online examination system for administrators, students and invigilators in the school of Electrical and Electronic Engineering (EEE) at Nanyang Technological University (NTU). However, the scope of this project is only focused on the development of students’ UI of the online examination system. After integrating administrators’ and invigilators’ UI, we have developed a secure online examination system for NTU’s school of EEE students that is capable of conducting examinations remotely from their homes. The results show that this system can minimize acts of cheating while still being able to fulfil the primary function of facilitating students to complete their registered examinations online.